2024
DOI: 10.1126/science.adl4606
|View full text |Cite
|
Sign up to set email alerts
|

Sister chromatid cohesion is mediated by individual cohesin complexes

Fena Ochs,
Charlotte Green,
Aleksander Tomasz Szczurek
et al.

Abstract: Eukaryotic genomes are organized by loop extrusion and sister chromatid cohesion, both mediated by the multimeric cohesin protein complex. Understanding how cohesin holds sister DNAs together, and how loss of cohesion causes age-related infertility in females, requires knowledge as to cohesin’s stoichiometry in vivo. Using quantitative super-resolution imaging, we identified two discrete populations of chromatin-bound cohesin in postreplicative human cells. Whereas most complexes appear dimeric, cohesin that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
2
2
0
Order By: Relevance
“…Together, these findings highlight the non-overlapping functionalities of the two cohesin forms. Our results are consistent with studies showing distinct mechanisms for cohesin mediated loop extrusion and chromatid cohesion 14,40 .…”
Section: Extrusive-cohesin Vs Cohesive-cohesinsupporting
confidence: 93%
See 2 more Smart Citations
“…Together, these findings highlight the non-overlapping functionalities of the two cohesin forms. Our results are consistent with studies showing distinct mechanisms for cohesin mediated loop extrusion and chromatid cohesion 14,40 .…”
Section: Extrusive-cohesin Vs Cohesive-cohesinsupporting
confidence: 93%
“…To decipher the potential influence of condensin on cohesive-cohesin, we sought to map the binding profile of Sororin, which selectively marks cohesive-cohesin 14,32 , in the absence versus the presence of condensin. Since Sororin is typically evicted from mitotic chromosome arms by CDK1/Aurora B mediated phosphorylation, we employed a previously characterized mutant form of Sororin, harboring nine evolutionarily conserved phosphosites mutated to alanine 34,35 (Extended Data Fig.…”
Section: Condensin Interrupts Cohesive-cohesin Focal Accumulation Ana...mentioning
confidence: 99%
See 1 more Smart Citation
“…Using structured illumination microscopy of the isoform-shared Cohesin subunit RAD21, it was recently reported that the majority of the loop-extruding Cohesin is present in dimers or multimers (Ochs et al, 2024). Consistent with this finding, our STED super-resolution imaging of isoform-specific Cohesin subunits revealed that the less abundant Cohesin-STAG1 is present as a monomer, but that the more abundant isoform Cohesin-STAG2 undergoes dimerization on chromatin in later G1 in a concentration dependent manner.…”
Section: The Oligomerization State Of Cohesinsupporting
confidence: 86%